A critical discourse study on Meghan and Harry’s CBS primetime interview - How, Cherish (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study focuses on Meghan and Harry’s narratives in the CBS Primetime interview with Oprah Winfrey where they highlighted the issues they faced before moving to America. During the interview, the couple raised several bombshells ranging from the lack of freedom, to Archie’s royal title and security, racism, and the lack of support and guidance from the Royal Family, which negatively portrayed the Royal Family and British tabloids. Using van Dijk’s ideological square model and its discursive strategies as a framework, this study examines how the Duke and Duchess of Sussex linguistically construct the self-other representations that are evident in their interview via critical discourse analysis and narrative inquiry approach. Findings show that the couple most commonly employed discursive strategies such as victimisation, vagueness, disclaimers, comparisons, evidentiality, hyperbole, history as a lesson, generalisation, pseudo-ignorance, implications, distancing, openness, and polarisation of us versus them. In doing so, they represented themselves as positive, while portraying the British tabloids and the Royal Family as the negative-other. Consequently, the use of language in this interview narrative may legitimise the Duke and Duchess of Sussex while suppress the Royal family and British tabloids. This paper is timely as it is only through in-depth analysis of the linguistic features that we are able to unveil ideological presupposition and biases underlying the interview. It also serves to educate the public that there is always more than one side to a story. Therefore, we should avoid having any biases or ideological presupposition towards anyone in any event before the truth is revealed from both sides.